TINJAUAN ONTOLOGIS ATAS KAJIAN INTEGRASI ISLAM DAN PSIKOLOGI : (Ontological Review of Integration Studies Islam and Psychology) - Jamil Abdul Aziz; Muhammad Safri Jamal (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2024)
The discourse on the concept of the integration of Psychology with Islam (ontology) in Indonesia from the beginning of its emergence in the 90s until now has never really got a single point of agreement or meaning. The most powerful debate crystallized in two groups, namely: